Leavening ability of yeast isolated from different local fruits in bakery product (Keupayaan Menaik Yis yang dipencilkan daripada Buah-Buahan Tempatan dalam Produk Bakeri) - Ma’aruf .A.G,; Noroul Asyikeen .Z,; Sahilah .A.M,; Mohd Khan .A, (Universiti Kebangsaan Malaysia, 2011)
This study focused on the isolation of yeast from a variety of Malaysian local fruits which can potentially be employed as a leavening agent in bakery products. A total of 6 yeast strains (SKS2, SMK9, SDB10, SRB11, SS12, SM16) were isolated from palm kernel pulp (Cocos nucifera L.), longan (Dimocarpus longan spp. malesianus Leenh), soursop (Annona muricata L.), bamboo shoot (Bambusa vulgaris), snake fruit (Salacca zalacca) and mango (Mangifera indica) using an enrichment procedure which can enhance the growth of yeast colonies and eliminat the fruits worm. The isolates were identified as Saccharomyces cerevisiae, through observation of the yeast cells morphology under microscope, temperature tolerance and fermentative capacity test. The leavening ability of the identified yeasts were examined by fermenting dough. Fermentation proofing was carried out at 30±5°C with 85% humidity for 120 min. The bread doughs were baked at 180°C for 8 min. Results showed that the yeast strains SRB11, SM16, SS12 and SMK9 were able to leaven the highest specific volume of 3.68 cm3/g, 3.41 cm3/g, 3.37 cm3/g and 3.23 cm3/g, respectively. Strain SDB10 and commercial yeast showed less ability with specific volume of 3.02 cm3/g and 2.84 cm3/g, respectively. Thus, the new yeast isolates from local fruits showed much superior with specific volume of more than 3.02 cm3/g.